Modelling and analysis of a complete adsorption heat pump system - Dias, João M. S. (2024)
Adsorption heat pumps (AHPs) can play a significant role in the future energy transition policies. However, the technology still needs to be matured and further research is still necessary. In this paper, the detailed model of a whole AHP system for domestic water heating is presented aiming to fulfil the literature gap for models that can simulate the dynamics of these complete heating systems, while maintaining a high level of modeling detail for the adsorbent bed. The model integrates all the main components of the AHP system, namely the evaporator, the condenser, the heater, the water reservoir and the adsorber. The adsorber is modeled by a 2D distributed parameter model with dynamic boundary conditions since the evaporator and condenser’s temperatures vary in a cycle as well as from cycle to cycle. The novel model obtains the detailed temperature, pressure, and uptake fields in the adsorbent bed when integrated in a complete AHP system. Real scale AHP systems should not be accurately modelled by lumped-parameter models due to the heterogeneities on the temperature, pressure, and uptake in the adsorbent bed. The time evolution of the system’s variables over five simulated cycles is obtained, as well as the coefficient of performance (COP) and specific heating power (SHP) of the whole system. For working conditions suitable for domestic water heating the system’s COP is 1.35 and the SHP is 79.3 W.kg−1.s−1.